Optimization of The Surface Crack on The Human Lumbar Vertebra - Zulkifli, Ahmad@Manap; K., Kadirgama (2013)
The goal of this study is to optimize the surface crack parameter of the lumbar spine using probabilistic and finite-element analysis. The model was constructed based on the actual size of vertebra. In order to simplified the model, vertebra was assumed as an isotropic, linear and symmetrical model with all components meshed by tetrahedral element whereas hexahedral for crack structure. Most of the vertebra fracture is caused by compressive loading due to the high-energy impact or lifting heavy goods. In addition, unilateral pedicle crack is close related to the compressive loading on the posterior region. However, this biological structure involved too many uncertainties in terms of mechanical properties, loading and geometry. Therefore, probabilistic analysis was performed to cater the problem that unsolved by deterministic analysis. Probabilistic and optimization techniques were used to measure the correlation between input parameters of the bone failure based on the yield stress and fracture toughness consideration. Furthermore, the sensitivity analysis will emphasize and validate the crucial parameters that should be stress and focus on the failure criteria.